Structure, function, and fate of the BlaR signal transducer involved in induction of beta-lactamase in Bacillus licheniformis. - Zhu, Y (1992)
The membrane-spanning protein BlaR is essential for the induction of beta-lactamase in Bacillus licheniformis. Its nature and location were confirmed by the use of an antiserum specific for its carboxy-terminal penicillin sensor, its function was studied by genetic dissection, and the structure of the penicillin sensor was derived from hydrophobic cluster analysis of the amino acid sequence by using, as a reference, the class A beta-lactamases with known three-dimensional structures. During the first 2 h after the addition of the beta-lactam inducer, full-size BlaR, bound to the plasma membrane, is produced, and then beta-lactamase is produced. By 2 h after induction, BlaR is present in various (membrane-bound and cytosolic) forms, and there is a gradual decrease in beta-lactamase production. The penicillin sensors of BlaR and the class D beta-lactamases show strong similarities in primary structures. They appear to have the same basic spatial disposition of secondary structures as that of the class A beta-lactamases, except that they lack several alpha helices and, therefore, have a partially uncovered five-stranded beta sheet and a more readily accessible active site. Alterations of BlaR affecting conserved secondary structures of the penicillin sensor and specific sites of the transducer annihilate beta-lactamase inducibility.